UPAYA PENCEGAHAN HIPERKOLESTEROLEMIA MELALUI PEMERIKSAAN SKRINING TEST DAN PENYULUHAN DI DESA KUMO KECAMATAN TOBELO, HALMAHERA UTARA - Asih Blandina, Olivia; Yulianti Hohedu, Ribka (HIRONO : Jurnal Pengabdian Masyarakat, 2022)
This community service was carried out for 1 day for the people of Kumo Village, Tobelo District, which aims to prevent hypercholesterolemia through Screening Tests and Counseling in Kumo Village, RT 03, Tobelo District. This activity was carried out by a lecturer in the Nursing Study Program, Hein Namotemo University. The method used is counseling and health checks. The implementation stage begins with counseling about gout, cholesterol, and blood sugar delivered by a lecturer in the Nursing study program at Hein Namotemo University, which is followed by discussions and questions and answers. Then proceed with a health check, especially cholesterol levels in the blood. The results of the health examination showed that the people of Kumo Village RT 03, Tobelo District had high cholesterol levels as many as 7 people and 6 people normal.